Can Chronic Ankle Instability Be Prevented? Rethinking Management of Lateral Ankle Sprains - Denegar, Craig R. (National Athletic Trainers Association, 2002)
Objective: To pose the question, “Can chronic ankle instability be prevented?” The evaluation and treatment of chronic ankle instability is a significant challenge in athletic health care. The condition affects large numbers of athletes and is associated with reinjury and impaired performance. The management of acute injuries varies widely but in athletic training has traditionally focused on initial symptom management and rapid return to activity. A review of practice strategies and philosophies suggests that a more detailed evaluation of all joints affected by the injury, correction of hypomobility, and protection of healing structures may lead to a more optimal long-term outcome. Background: Sprains to the lateral ankle are common in athletes, and the reinjury rate is high. These injuries are often perceived as being isolated to the anterior talofibular and calcaneofibular ligaments. It is, however, becoming apparent that a lateral ankle sprain can injure other tissues and result in joint dysfunction throughout the ankle complex. Description: We begin by addressing the relationship between mechanical and functional instability. We then discuss normal ankle mechanics, sequelae to lateral ankle sprains, and abnormal ankle mechanics. Finally, tissue healing, joint dysfunction, and the management of acute lateral ankle sprain are reviewed, with an emphasis on restoring normal mechanics of the ankle-joint complex. A treatment model based on assessment of joint function, treatment of hypomobile segments, and protection of healing tissues at hypermobile segments is described.